2016
DOI: 10.1177/0272989x16662654
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment for Venous Thromboembolism in Chemotherapy-Treated Ambulatory Cancer Patients

Abstract: Although the monocentric validation of the presented predictors might represent a limitation, these results demonstrate that a model based on MKL and RO may represent a novel methodological approach to derive VTE risk classifiers. Moreover, this study highlights the advantages of optimizing the relative importance of groups of clinical attributes in the selection of VTE risk predictors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 34 publications
1
63
0
Order By: Relevance
“…The machine learning algorithms used in our study were Random Forests, Artificial Neural Network and Support Vector Machine, because they are among the algorithms that are currently most widely and successfully used for clinical data (27). Each one of them represents a different algorithm “family,” each with radically different internal algorithm structures (16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The machine learning algorithms used in our study were Random Forests, Artificial Neural Network and Support Vector Machine, because they are among the algorithms that are currently most widely and successfully used for clinical data (27). Each one of them represents a different algorithm “family,” each with radically different internal algorithm structures (16).…”
Section: Methodsmentioning
confidence: 99%
“…Machine learning belongs to the domain of artificial intelligence and provides a promising tool in pursuing personalized outcome prediction, which is increasingly used in medicine (27). The machine learning methodology allows discovering empirical patterns in data through automated algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Chatbots 1 [39,37] have conquered our new window-on-the-world -our smartphonesand, from there, they help with everyday tasks such as managing our agenda, answering our factoid questions or being our learning companions [16,4]. In medicine, computers can already help in formulating diagnoses [2,18,10] by looking at data doctors generally neglect. Artificial Intelligence is preparing a wonderful future where people are released from the burden of repetitive jobs.…”
Section: Introductionmentioning
confidence: 99%
“…Authors in [15] used Gated Recurrent Unit [16] combined with Support Vector Machine [17] algorithms for diagnosing breast cancer on WDBC dataset. Some of the research works have used multiple kernel learning [18] method for various healthcare problems [19][20] and provides the way to examine the learned model. One of the authors combined SVM [21] and Random optimization [22] methods for demographic, clinical and biochemical data prediction.…”
Section: Related Workmentioning
confidence: 99%
“…From the table-4, it is concluded that proposed CNN outperforms than the other approaches and it is decided that it is highly suitable for medical image processing and analyzation. To evaluate the performance of the proposed CNN, the obtained accuracy is compared with the existing research works, have carried out the similar research works given in author in [17] obtained 60% on DDSM dataset, author in [18] obtained 88% on BCDR-F03 dataset, Duraisamy&Emperumal (2017) obtained 85% on MIAS and BCDR dataset and author in [19] obtained 60% on CBIS-DDSM dataset. From the overall existing system, author in [19] obtained the highest accuracy.…”
Section: Datasetmentioning
confidence: 99%